Magnetron sputtered coatings of AlN-TiCrB₂ system - Panasyuk, A.D.; Podchernyaeva, I.A.; Neshpor, I.P.; Gawalek, W.; Ivanov, V.N. (Functional Materials, 2009)
Wear and corrosion resistant coatings have been obtained by HF magnetron sputtering of an AlN-TiCrB₂ target (prepared by powder metallurgy technique) on Si, Al₂O₃ and GaAs single crystals. The coatings are characterized by ultra dispersed structure and a considerable high-temperature oxidation resistance caused by the formation of solid solutions in the Al₂O₃-TiO₂-Cr₂O₃ and Al₂O₃-B₂O₃ systems. The target material mass gain at 1300°C is 1.4 mg/cm². After the high-temperature oxidation, a reinforced disperse structure is formed in the coating as tangled Al₂O₃ fibers. The (AlN-TiCrB₂)-Al₂O₃ and (AlN-TiCrB₂)-GaAs coatings are thermally stable up to 900°C and show high microhardness (Hμ = 30 GPa) and fracture strength (K₁c = 3.3-4.7 MN/m³/²). As the annealing temperature rises (T > 1000°C), the coating mechanical properties deteriorate but its adhesion strength becomes improved. The target material AlN-TiCrB2 can be recommended to prepare wear and corrosion resistant coating on tools as well as on vital parts being operated in extreme conditions.